Image: its power, use, and abuse - Rehman, Sharaf (Scripta Neophilologica Posnaniensia, 2019)
This position paper addresses three areas in which photographic images are used and abused: Journalism, Advertising, and Public Relations. These areas do not use images for aesthetic purposes only; for these businesses, the images are more than mental impressions. In these three industries, the messages they deliver through the images have little to do with the objective reality. All three use images to deliver an opinion in the name of journalism, distorted needs, benefits, and solutions in advertising, and put spins on facts to present favorable images of their clients in Public Relations. Historically, all three have engaged in the unethical use of the concept “image making” and of manipulation of actual images.